Analisis Keabsahan Perjanjian Transaksi E-Commerce pada Aplikasi Shopee yang Dilakukan oleh Anak di Bawah Umur - Dani Baskoro, Ale; Susetio, Wasis (CV Rewang Rencang, 2026)
The development of digital technology has provided convenience for the community, especially with the presence of the Shopee marketplace application. However, this convenience also presents various challenges and obstacles in its implementation related to the validity and technical mechanisms of the business actor's accountability pattern so that it is easily managed by minors. This study aims to analyze the validity of contracts and the liability of the Shopee marketplace in the event of a legal violation by a minor by referring to the Civil Code and Law Number 1 of 2024. The method used by the author is a normative legal research method with a regulation-based approach that is studied conceptually. The results of the study indicate that electronic transactions carried out by minors on the Shopee application are legally invalid because they are contrary to Article 1320 of the Civil Code regarding reasons of competence and are invalid due to reasons of agreement where the Shopee application uses a Terms & Conditions policy that contains the requirements and policies of e-commerce transactions where underage users subjectively do not have the competence to understand the contents and standard clauses of the sales and purchase agreement. This study recommends that the Shopee application update its technical mechanisms for users regarding usage permissions that stipulate minimum age requirements in an effort to prevent future legal disputes.